2023
DOI: 10.1007/s12144-023-04331-8
|View full text |Cite
|
Sign up to set email alerts
|

How and when can job-insecure employees prevent psychological distress against the COVID-19 pandemic? The role of cognitive appraisal and reappraisal

Abstract: The COVID-19 pandemic has greatly affected economies around the world, causing record unemployment rates that have exacerbated the already prevalent job insecurity, thereby leading to psychological distress among many individuals. The present study aims to reveal the underlying mechanisms of psychological distress induced by the COVID-19 pandemic among job-insecure employees and to identify one of the emotion regulation strategies (i.e., cognitive reappraisal) as a protective factor that mitigates psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…Factors such as job anxiety can moderate the relationship between people's beliefs and their psychological well-being (Lent & Brown, 2008). In addition, research has shown that factors such as age and gender can impact people's perceptions of chatbots (Capone et al, 2023;Wang et al, 2023).…”
Section: Social Cognitive Theorymentioning
confidence: 99%
“…Factors such as job anxiety can moderate the relationship between people's beliefs and their psychological well-being (Lent & Brown, 2008). In addition, research has shown that factors such as age and gender can impact people's perceptions of chatbots (Capone et al, 2023;Wang et al, 2023).…”
Section: Social Cognitive Theorymentioning
confidence: 99%
“…Factors such as job anxiety can moderate the relationship between people's beliefs and their psychological well-being (Lent & Brown, 2008). Additionally, research has shown that factors such as age and gender can impact people's perceptions of chatbots (Capone et al, 2023;Wang et al, 2023).…”
Section: Theoretical Frameworkmentioning
confidence: 99%